The Influence of Bioinsecticide Granules of Srikaya (A. Squamosa) and Betel Leaves (P. Beetle) Extract Extracts on Kidney Histopathology in Mice (Mus musculus) - Wike Rosalini; Sri Hernawati; Dwi Wahyuni (Alliance oh Health Activists (AloHA), 2020)
The use of chemical insecticides in the long term and high frequency will suppress insects (mosquitoes) and vectors to be tolerant until resistant. Reports of resistance from various species of mosquitoes found in multiple countries even occur in Indonesia in Surabaya. This study aimed to analyze the effect of granules bioinsecticides on the mixture of srikaya seeds (A. squamosa) and betel leaf (P. beetle) on the histopathology of mice (M. musculus) using true-experimental (the post-test only group design). Sample taken by simple random sampling and grouped into each control group and the treatment group totaling 25 mice. Data were analyzed using simple linear regression test. The results showed an overall p-value >0.05, meaning that there was no bioinsecticide effect of a mixture of betel leaf granules (Piper beetle) and srikaya seeds (Annona squamosa) on the histopathology of the kidney of mice (Mus musculus). Required safety testing of target animals in addition to mice and a preliminary examination is needed before the research is conducted so that the results are valid Keywords: bioinsecticide; histopatology; Mus musculus